Engaging the private sector to strengthen NCD prevention and control - Allen, L; Bloomfield, A; Working Group of the Global Coordination Mechanism on NCDs (Elsevier, 2016)
All around the world private enterprises influence health through the sale of both harmful and health-promoting commodities, as well as lobbying and marketing activities. As globalisation further strengthens the role of the private sector as a major driver of the non-communicable disease (NCD) pandemic, engaging with the private sector to prevent and control these conditions has become increasingly important. In recognition of this fact, the 2011 UN High-Level Political Declaration on NCDs2 called on the private sector to take action in areas such as promoting healthy workplaces, improving affordability and access to medicines, and reformulating unhealthy food products. In 2014, Ministers at the UN General Assembly noted that limited progress had been made in these areas. The 67th World Health Assembly established a working group (under the auspices of the Global Coordination Mechanism on NCDs) to develop more granular recommendations for governments. This Comment provides an overview of these recommendations, which are described in detail in its full report.